Connecting Mitochondria, Metabolism, and Stem Cell Fate - Wanet, Anaïs; Arnould, Thierry; Najimi, Mustapha; Renard, Patricia (Stem cells and development, 2015)
As sites of cellular respiration and energy production, mitochondria play a central role in cell metabolism. Cell differentiation is associated with an increase in mitochondrial content and activity and with a metabolic shift toward increased oxidative phosphorylation activity. The opposite occurs during reprogramming of somatic cells into induced pluripotent stem cells. Studies have provided evidence of mitochondrial and metabolic changes during the differentiation of both embryonic and somatic (or adult) stem cells (SSCs), such as hematopoietic stem cells, mesenchymal stem cells, and tissue-specific progenitor cells. We thus propose to consider those mitochondrial and metabolic changes as hallmarks of differentiation processes. We review how mitochondrial biogenesis, dynamics, and function are directly involved in embryonic and SSC differentiation and how metabolic and sensing pathways connect mitochondria and metabolism with cell fate and pluripotency. Understanding the basis of the crosstalk between mitochondria and cell fate is of critical importance, given the promising application of stem cells in regenerative medicine. In addition to the development of novel strategies to improve the in vitro lineage-directed differentiation of stem cells, understanding the molecular basis of this interplay could lead to the identification of novel targets to improve the treatment of degenerative diseases.